Analisis Risiko Pelaksanaan Proyek Konstruksi Gedung Perawatan Paru dan HIV BLUD Rumah Sakit Umum Daerah Nabire - Mozart Riliandi; Josefine E Latupeirissa; Herby Calvin P Tiyouw (Paulus Civil Engineering Journal, 2021)
This study aims, to analyze, risk, project implementation, construction, building, pulmonary care and HIV BLUD general hospital Nabire area. Especially at the risk of implementation. Data collection in the form of interviews and questionnaires to staff is projected. The result of analysis of 20 risk factors for project implementation stated that material loss was 30%, material damage was 32.5%, material scarcity in the market 30%, delays in delivery of materials from suppliers 82.5%, material price increase of 32.5%, change order 70%, lack of inventory control 77.5%, lack of control and construction in the team 30%, lack of labor 32.5%, indiscipline of workers 35%, theft of materials 77.5%, unexpected cost 82.5%, high frequency of job changes 32.5%, frequent job delays of 32.5%, uncontrollable financial control 77.5%, under-controlled reporting system 87.5%, frequent changes in economic conditions 37.5%, bad weather out of control 80%, the number of jobs that have to be replaced due to defects or wrong 40%, frequent occurrences of unexpected things during the implementation of construction 82.5%. The average value above 50% in the range is influential until it is very influential. Thus it can be concluded that the risk is very influential in the implementation of construction projects.